Application and verification of new design method by high-strength composite material - Haruhiko IIDA; Hidetoshi SAKAMOTO; Yoshifumi OHBUCHI; Toshiaki FUJISHIMA (Nihon Kikai Gakkai ronbunshu, 2015)
The purpose of this research is the application of new design method for integrating the optimum strength evaluation and the product design which can make the best use of the composite material's characteristics obtained by the experiment and the analysis. Here, the collaboration of the design and the strength analysis by using composite materials is carried out. The products, which are made from high strength composite materials, need new product design technology which draws out the characteristic of material's advantage. Existing product developments tend to separate product design from product planning. The process consists of a certain flow, starting from planning the shape of the product by designers, then calculating the strength, and lastly designing the product. In the new design method, it is performed a styling design by requirements from the engineering point of view. By using this design method of high-strength materials, we designed new styling ZIGZAG Chair made of the carbon fiber reinforced plastic with excellent strength and lightweight. And then, analyzed it.